1984
DOI: 10.1515/zna-1984-0714
|View full text |Cite
|
Sign up to set email alerts
|

Quantenchemische Rechnungen am Borin (Borabenzol)

Abstract: Quantumchemical Calculations on Borine (Borabenzene)Although many Borinato-transition metal-complexes have been isolated after the first synthesis and characterisation of such a molecule in 1970, nobody succeeded so far in isolating the unsubstituted neutral ligand Borine (Borabenzene) C5H5B.It is the aim of this theoretical investigation to find at least a partial answer to the question why the free borine should be a highly reactive molecule.The results of semiempirical and ab-initio-calculations presented h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Using the MP2/6-311þþG** and the UMP2/6-311þþG** energies including zero point energies for the singlet and the triplet state 1T is energetically 54.6 kcal mol À1 above 1S, which is about twice the modified neglect of diatomic overlap (MNDO) value previously obtained with the half electron method. [1] A value of /S 2 S ¼ 2.34 indicates that at this level the lowest triplet state is significantly contaminated by higher spin states. Annihilation of these components using projected MP2 (PMP2) [24] and the same basis set resulted in a somewhat smaller singlet-triplet splitting of 45.3 kcal mol À1 and /S 2 S ¼ 2.05.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the MP2/6-311þþG** and the UMP2/6-311þþG** energies including zero point energies for the singlet and the triplet state 1T is energetically 54.6 kcal mol À1 above 1S, which is about twice the modified neglect of diatomic overlap (MNDO) value previously obtained with the half electron method. [1] A value of /S 2 S ¼ 2.34 indicates that at this level the lowest triplet state is significantly contaminated by higher spin states. Annihilation of these components using projected MP2 (PMP2) [24] and the same basis set resulted in a somewhat smaller singlet-triplet splitting of 45.3 kcal mol À1 and /S 2 S ¼ 2.05.…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] In those calculations, we found that borabenzene in its ground state is planar, and like benzene, pyridine, and other aromatics, has three doubly occupied orbitals of p symmetry. However, its lowest unoccupied molecular orbital was found to be of s symmetry and to be mainly located at the boron atom.…”
Section: Introductionmentioning
confidence: 87%
“…Borabenzene 1 is a nonexistent aromatic heterocycle. The elusive nature of 1 , according to quantum chemistry calculations at different levels, is due to the presence of a low-lying in-plane σ-type LUMO which is essentially localized at the boron atom . This highly reactive species, however, can be stabilized either by uncharged donors to afford neutral borabenzene−Lewis base adducts , (e.g., 2 3a ) or by anionic groups to give boratabenzene ions , (e.g., 3 5a ).…”
mentioning
confidence: 99%
“…Borabenzene (C 5 H 5 B) has been the subject of some experimental [1][2][3] and an even higher number of theoretical [4][5][6][7][8][9][10][11][12] studies; however, attempts to generate the free compound have met with failure so far. At least in two experimental studies, borabenzenze apparently occurred as a transient that was trapped either by dinitrogen [1] or pyridine.…”
Section: Introductionmentioning
confidence: 99%